Utilization of hydrolyzed corncob as a carbohydrate source in diets for red Nile tilapia Oreochromis niloticus - Fauzan; Muhammad Agus Suprayudi; Ichsan Achmad Fauzi; Julie Ekasari (Jurnal Akuakultur Indonesia)
This study was aimed to evaluate the influence of corncob hydrolysis on its crude fiber content, digestibility level, and utilization in the red Nile tilapia diet. This study was performed in two steps, namely hydrolysis and digestibility test. The first study step was enzymatic hydrolysis using 0.4 g/kg cocktail enzyme, followed by chemical hydrolysis using hydrochloric acid (HCl) at different treatments, i.e. concentration, incubation period, and ratio. The second step was designed using a completely randomized design with five treatments, i.e. Rd (reference diet), TJt15% (15% unhydrolyzed corncob), TJt30% (30% unhydrolyzed corncob), TJh15% (15% corncob hydrolysis), and TJh30% (30% corncob hydrolysis). The average weight of tilapia was 15.86 ± 0.19 g/fish. The hydrolyzed corncob meal used for the second study step from the hydrolysis production could reduce 57.53% of crude fiber, 38.15% of NDF fiber fraction, 6.43% of ADF fiber fraction, and 61.96% of hemicellulose. The digestibility test results showed that the hydrolyzed corn cob diet obtained a higher digestibility level, digestive enzyme activity, and blood plasma protein than the unhydrolyzed corncob diet (P<0.05). This study concludes that the corncob hydrolysis eliminates the crude fiber content, fiber fraction contents (NDF, ADF, and hemicellulose), and improves the digestibility level of red Nile tilapia.